Exploring the cultural identity of Ebleg Kebumen: An ethnographic approach - Nazla Maharani Umaya; Setia Naka Andrian; Nindya Juniarti (International Journal of Culture and Art Studies, 2026)
This study explores the traditional performing arts of Ebleg and Kuda Lumping in Central Java, Indonesia. Using a qualitative methodology with an emic perspective, the research examines the social context, participants, and activities associated with these performances. Ebleg, rooted in Kebumen's cultural heritage, showcases unique costumes and narratives that reflect local identity and history. The findings reveal how these performances serve as mediums for cultural expression and community solidarity, while also highlighting the challenges of preserving such traditions amid an aging performer population and declining interest from younger generations. The study underscores the importance of community involvement in cultural preservation and advocates broader engagement to ensure the continuity and evolution of Ebleg as a vital aspect of local heritage. Ultimately, this research contributes to understanding the dynamic interplay between traditional arts and contemporary cultural identity in Indonesia.